Acquiring Syntactic Translation Rules from a Parallel Treebank - Colhon, Mihaela (Infotheca - Journal for Digital Humanities; Vol 13 No 2 (2012): Infotheca - Journal of Informatics and Librarianship, 2024)
The presented study addresses the issue of machine translation system development,as it makes use of a parallel syntactic phrase extraction algorithm in order to obtaina rich and robust set of syntactic translation patterns. To make this approach feasible, only phrase-to-phrase alignments from a bilingual treebank with syntactic constituents are considered. The knowledge enclosed in this study is defined by means of syntactic motivated translation sequences, written in terms of the morpho-syntactic specifications developed during the MULTEXTEast Project (Erjavec, 2010).